2019
DOI: 10.1111/epi.16301
|View full text |Cite
|
Sign up to set email alerts
|

Acquired cardiac channelopathies in epilepsy: Evidence, mechanisms, and clinical significance

Abstract: There is growing evidence that cardiac dysfunction in patients with chronic epilepsy could play a pathogenic role in sudden unexpected death in epilepsy (SUDEP). Recent animal studies have revealed that epilepsy secondarily alters the expression of cardiac ion channels alongside abnormal cardiac electrophysiology and remodeling. These molecular findings represent novel evidence for an acquired cardiac channelopathy in epilepsy, distinct from inherited ion channels mutations associated with cardiocerebral pheno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 99 publications
(295 reference statements)
0
43
0
Order By: Relevance
“…Another possible explanation for the occurrence of ventricular tachycardia in patients with epilepsy, according to recent literature, is that through certain mechanisms yet unknown, epilepsy has caused a "pro-arrhythmic" state. For example, animal studies have shown that seizure activity alters the expression of ion channels in the heart, leading to abnormal ventricular repolarization and greater susceptibility to ventricular arrythmias and QTc prolongation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the occurrence of ventricular tachycardia in patients with epilepsy, according to recent literature, is that through certain mechanisms yet unknown, epilepsy has caused a "pro-arrhythmic" state. For example, animal studies have shown that seizure activity alters the expression of ion channels in the heart, leading to abnormal ventricular repolarization and greater susceptibility to ventricular arrythmias and QTc prolongation (15).…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analysis by Chahal et al suggested potential overlap between SUDEP and arrhythmogenic SCD with a common genetic ion channel abnormality that affects electrophysiology of both neurons and cardiomyocytes (cardiocerebral ion channelopathy) (Chahal et al, 2020), also supported by some case reports (Heron et al, 2010;Parisi et al, 2013). Acquired myocardial alteration secondary to refractory epilepsy may enhance vulnerability to develop lethal ventricular arrhythmias (Li et al, 2019;Verrier et al, 2020). The mechanisms underlying epilepsy-induced SCD are multifactorial and, in part, attributed to a dynamic interplay between heart and CNS (Li et al, 2019;Tolstykh and Cavazos, 2013).…”
Section: Heart-cns Axis In Scdmentioning
confidence: 99%
“…Acquired myocardial alteration secondary to refractory epilepsy may enhance vulnerability to develop lethal ventricular arrhythmias (Li et al, 2019;Verrier et al, 2020). The mechanisms underlying epilepsy-induced SCD are multifactorial and, in part, attributed to a dynamic interplay between heart and CNS (Li et al, 2019;Tolstykh and Cavazos, 2013). Hefti et al performed detailed neuropathological investigations and reported that nearly half of children with unexplained death (n = 69) had hippocampal malformation (Hefti et al, 2016).…”
Section: Heart-cns Axis In Scdmentioning
confidence: 99%
“…studies have deeply investigated the pathophysiology of SUDEP, and there is agreement that cardiac dysfunction plays a major role. [19] These studies have demonstrated that a severe depression of the cardiac and respiratory centers may arise after a generalized tonic-clonic seizure, particularly among young patients, and this fact can provoke severe hypoxemia and/ or hypotension, leading to an instant death [20]. On the other hand, among cardiac dysfunction causes there is lack of evidence for the existence of malignant ventricular arrhythmias in the context of epilepsy.…”
Section: Plos Onementioning
confidence: 99%